Injury prediction in competitive runners with machine learning - Lövdal, S. S.; Den Hartigh, R. J. R.; Azzopardi, G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Staying injury free is a major factor for success in sports. Although injuries are difficult to forecast, novel technologies and data-science applications could provide important insights. Our purpose was to use machine learning for the prediction of injuries in runners, based on detailed training logs.